(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Grab Food now has the widest restaurant selection in the Philippines, with 4,000 locally- based restaurants onboard. Grab Food continues to satisfy more cravings as it brings greater convenience to its consumers. We know Filipino consumers love a variety of food choices, so we’ve worked hard over the past months to bring onboard their local favorite merchants onto Grab Food. Today, we have the widest selection of restaurants on Grab Food. Food remains a top household expenditure in the Philippines, and we believe our on- demand food delivery service can add convenience to consumers’ lives while opening up more income streams for the merchant- and delivery partners. Grab keeps empowering its intricate network of customers, merchants, and delivery companies. Grab Food is improving how well it can make use of shared digital economy prospects. The results of this study reveal that the profile of the respondents in terms of age, sex, and length of service and also the customer treatment that affects the resiliency of food delivery riders was evaluated as "strongly agree" in terms of job performance, and job satisfaction, while behavior was evaluated as "agree; The problems encountered in terms of mistakes in order had the highest rank. This chapter includes a summary of the findings gathered from the study and what the study suggested. This includes the totality of outcomes of the conducted and the conclusions, and this study recommends that a way to increase the resiliency of food delivery riders is to improve their handling of customer orders because it is within the rules of the company to take care of the customer's orders. Doing so can increase the probability of obtaining a good rating from the customers and also improve proper food handling because proper food handling may encourage riders to be more careful and mindful of how they handle food.